MODELING THE DURATION OF THE RETURN LABOR MIGRATION OF THE POPULATION OF THE REGION ON THE EXAMPLE OF KALMYKIA - E. Kovanova; N. Eldyaeva (Вестник университета)
The process of internal labor migration of the population of the Republic of Kalmykia and shows its econometric modeling is considered. The Republic is characterized by a significant share of the outgoing population beyond its borders. High labor mobility is connected with economic reasons, which is confirmed by the data of the sample survey. In the study of the consequences of migration processes in the dynamics of the development of the region is of interest econometric methods that allow to assess the direction, the nature of the impact of a complex of socio-economic factors on its final results and consequences. The econometric approach has made it possible to link the factors and consequences of migration in a single analysis. As the results of the simulation has been showed, the time period of labor migration, the amount of income received by labor migrants, the age and level of education of migrants are in close dependence.